Hubungan Pola Asuh Orang Tua dengan Pertumbuhan dan Perkembangan pada Anak Pra-Sekolah di TK GMIM Syalom Matungkas - Likiliay, Paulina; Gannika, Lenny; Nisa, Khairun (Mapalus Nursing Science Journal, 2025)
Background: Preschool-aged children (4–6 years old) are in a critical period of growth and development that determines the quality of the next generation. During this stage, parenting plays a crucial role in optimizing the child’s physical, cognitive, social, and emotional potential. Objective: This study aims to analyze the relationship between parenting styles and the growth and development of preschool children at TK GMIM Syalom Matungkas. Method: The study used an analytic descriptive design with a cross-sectional approach. Data were collected through parenting style questionnaires as well as measurements of children's growth and development, then analyzed to examine the relationships between variables. Results: The gamma statistical test showed a p-value of 0.000 (p < 0.001), indicating a significant correlation, with an r-value of 0.518, which represents a moderately strong correlation. Conclusion: There is a significant relationship between parenting styles and the development of preschool children at TK GMIM Syalom Matungkas. However, no significant correlation was found between parenting styles and children's growth. Democratic parenting is highly recommended to support optimal growth and development in children. Keywords: Preschool Children, Development and Growth, Parenting Styles